(untitled) (International Journal of Technology and Management Research, 2021)
The study explored perceptions on the usage of Turnitin Plagiarism checking software among the staff of Koforidua Technical University (KTU) in Ghana. The research sought to explore the associations between the independent variables (Attitude and Perception, Perceived Challenges and Readiness to Use) and the dependent variable (System Usage) of the Turnitin Software among the staff of KTU. The survey adopted the quantitative research approach. Google forms were used to design questionnaires and mailed to the participants. The response rate valid for analysis was 98.7%, against a sample size of 309 participants. SmartPLS3 software was used to explore the data extracted from google forms. The results of the convergent, discriminant validity calculation were all within the satisfactory threshold. Four hypothetical statements were tested, three of them showed significant association with the independent variables (Attitude and Perception, Perceived Challenges and Readiness to Use) and dependent variable (System Usage) except System Awareness which was not supported and rejected. The proposed model explained 66.7% invariance of the System Usage (Turnitin Software). The study recommends continuous dissemination of information about the availability of the Turnitin Software in the University. Citation: Asante, E., Baayel, P., Adjei, B., K.W., and Owusu-Acheaw, M. (2021). Perception of Turnitin: Checking Plagiarism among Staff at Koforidua Technical University (KTU), Ghana. International Journal of Technology and Management Research (IJTMR), Vol. 6 (1): Pp.116-128. Received: March 20, 2021 Accepted: September 1, 202